Engaging and transforming global communication through cultural discourse analysis: a tribute to Donal Carbaugh - Scollo, Michelle; Milburn, Tracy (2023)
The book is a handbook of cultural discourse analysis, a theory developed by Donal Carbaugh, and celebration of his work. The book features an explanation of the theory and sixteen chapters using ...
Keywords: dept.aa